Behind the Hammer's Swing: Work Fatigue Among Traditional Stone Breakers in the Coastal Region of the Selayar Islands, Indonesia - Maharja, Rizky; Tajuddin, Tajuddin; Rahmansyah, Sitti Fatimah; Kessi, Andi Tenriola Fitri; Juliani, Arni; Maharja, Riadnin (Diversity: Disease Preventive of Research Integrity, 2024)
The work of stone breakers involves heavy and repetitive physical activity, which can increase the risk of injuries and health problems, one of which is work fatigue. Before work fatigue becomes more severe, it is essential to identify its causes. This study aims to analyze work fatigue and the factors that influence it. The study uses an observational analytic approach with a total of 50 respondents. The variables measured include age, length of work, years of service, workload, total sleep time, and work fatigue. Data collection was carried out through questionnaires and specific workload observations. The results of the study indicate that 25 people (50%) experienced high work fatigue. Further analysis showed that age (p-value = 0.020) and gender (p-value = 0.001) significantly influenced work fatigue. The results also showed that there was no significant effect of length of work (p-value = 0.140), years of service (p-value = 0.27), workload (p-value = 0.258), and total sleep time (p-value = 0.401) on work fatigue. This study concludes that work fatigue among traditional stone breakers is influenced by age and gender. Interventions are needed to reduce work fatigue through adjustments to the work environment and rest periods. This study reinforces the understanding of Q.S. Al-Baqarah/2:286, which emphasizes that every individual has limitations. The fatigue experienced is proof that the human body has limits and needs adequate rest to function optimally.